2012
DOI: 10.1136/jfprhc-2011-100244
|View full text |Cite
|
Sign up to set email alerts
|

Family planning providers' perspectives on family planning service delivery in Ibadan and Kaduna, Nigeria: a qualitative study

Abstract: ObjectiveIn Nigeria, fertility continues to be high and contraceptive prevalence remains low. This study was conducted in order to understand the perceptions of, experiences with and challenges of delivering family planning services in two urban areas of Nigeria from the perspectives of family planning service providers.MethodsA qualitative study using 59 in-depth interviews was conducted among family planning providers working in hospitals, primary health centres, clinics, pharmacies and patent medicine vendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Mystery client visits indicated that less than 15% of customers purchasing birth control pills were informed about side effects [ 40 , 78 ]. Some PPMVs expressed the need to maintain good communications, discretion, and confidentiality when dispensing family planning products to young customers [ 63 ], however others indicated that they may exclude youth and unmarried customers from receiving family planning services [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mystery client visits indicated that less than 15% of customers purchasing birth control pills were informed about side effects [ 40 , 78 ]. Some PPMVs expressed the need to maintain good communications, discretion, and confidentiality when dispensing family planning products to young customers [ 63 ], however others indicated that they may exclude youth and unmarried customers from receiving family planning services [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Client use of FP services in Pakistan has been associated with FP training experience of providers [21]. Prior research from Nigeria has indicated that family planning (FP) training among providers offering FP is actually rare [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Evidence also exists of health facility barriers in method choice, including staff levels, expired stock, provider bias, and lack of training in Nigeria and other developing countries [3] , [17] , [18] , [19] . The general medicalization of family planning and the clinic-based nature of distribution has been criticized as a barrier to increasing levels of contraceptive use [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%